Kemampuan Berpikir Kritis Pada Pembelajaran Pkn Menggunakan Model PBL Berbasis Treasure Hunt Dan QR Code - Anatasia Riantika; Sutrisna Wibawa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In the era of revolution 4.0, education does not only require intellectual abilities, but critical thinking, creative, communicative and collaboration skills. The problem with Civics learning is that it still prioritizes cognitive aspects, it has not been able to realize the goal of creating critical and responsible students. There needs to be innovation in Civics learning that combines problem-based learning models through games and is integrated with the use of technology in elementary schools. This research aims to find out the influence of problem based learning implemented through the QR code-assisted treasure hunt game on Civics learning. The research method used is descriptive qualitative. The analysis technique used is an interactive analysis model consisting of data reduction, data presentation, and drawing conclusions or verification. The results of data analysis are presented in the form of descriptions supported by observations, interviews and literature studies. The results of the analysis and discussion can be concluded that critical thinking skills emerge in Civics learning using the PBL treasure hunt and QR code models. Critical thinking skills are demonstrated by the emergence of the following indicators: providing simple explanations, building basic skills, concluding, making further explanations, strategies and tactics. It is hoped that the results of this study can become a reference, especially in the field of education, to create a superior and characterful next generation.